2000
DOI: 10.1159/000026690
|View full text |Cite
|
Sign up to set email alerts
|

Genome Scan for Susceptibility Loci for Schizophrenia

Abstract: Objective: Schizophrenia is a relatively common, often chronic and debilitating mental illness. Evidence from various studies has clearly demonstrated that genetic factors contribute substantially to the etiology. The goal of this study was to identify chromosomal regions likely to contain schizophrenia susceptibility genes. Methods: A genome-wide map of 388 microsatellite DNA markers was genotyped in 5 schizophrenia families. Nonparametric linkage analysis (Genehunter) was used to assess the pattern of allele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0
2

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 22 publications
3
54
0
2
Order By: Relevance
“…26,39 Support for this focus also comes from linkage and association studies in BPD 38,48,49 and from a meta-analysis of linkage studies in BPD 5 as well as from the presence of AHI1, a gene causing a severe neuropsychiatric disorder (Joubert Syndrome) in this location. Weaker positive results in linkage studies of SCZ and BPD were also demonstrated distal to this focus 28,40,47 and may represent poorer localization of the same locus. Suggestive evidence for linkage distal to F-4 was also demonstrated for a modifier gene in Huntington's disease.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…26,39 Support for this focus also comes from linkage and association studies in BPD 38,48,49 and from a meta-analysis of linkage studies in BPD 5 as well as from the presence of AHI1, a gene causing a severe neuropsychiatric disorder (Joubert Syndrome) in this location. Weaker positive results in linkage studies of SCZ and BPD were also demonstrated distal to this focus 28,40,47 and may represent poorer localization of the same locus. Suggestive evidence for linkage distal to F-4 was also demonstrated for a modifier gene in Huntington's disease.…”
Section: Discussionmentioning
confidence: 89%
“…The first focus (from proximal to distal) of interest on chromosome 6q (F-1) is centered at 96 Mb with significant results for SCZ-related disorders demonstrated by two studies, 25,27 and supported from findings in SCZ, 24,26,28,30 and for both SCZ and BPD. 39 The second focus of findings (F-2) is at 105 Mb, mainly in BPD, with one significant study 42 and several supporting studies, 37,38,46 but also studies on SCZ, 24 autism 52 and multiple sclerosis.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Algumas regiões são relatadas como positivas para linkage em relação à esquizofrenia sobreposta a regiões de positividade para transtornos afetivos: 18p11.2 (Schwab, 1998); 13q32 (Blouin, 1998), 22q11 (Kelsoe, 2001) e 3q (Bailer, 2002). Existem relatos de linkage tanto da esquizofrenia quanto do transtorno bipolar para o cromossomo 6, mas com a limitação da possibilidade de comparação dos resultados em razão do uso de marcadores e modelos diferentes (Cao et al, 1997;Bailer et al, 2000).…”
Section: História Familiar De Esquizofrenia No Transtorno Bipolarunclassified